Peat moss Sphagnum riparium follows a circatrigintan growth rhythm in situ: A case report. (9th August 2017) - Mironov, V. L.; Kondratev, A. Y.
ABSTRACT: In situ growth of Sphagnum riparium Ångstr. shoots were monitored during the 2015 and 2016 growing seasons in Karelia, Russia. It was established that shoot growth rates fluctuated with a period of around 30 days, that is, showed a circatrigintan rhythm. Such rhythms from mosses have not been previously reported. Correlation of growth rates with the percentage of the illuminated portion of the Moon was statistically significant (p<0.01) in both years. Shoot growth rates were reliably higher around the new Moon compared to the full Moon. This phenomenon may be due either to causality or to a pure coincidence of processes with similar rhythms.